Risk Management in the Activities of International Banks in the Financial Market - Ying Guan; Vladimir Grigoriev (Communications of International Proceedings, 2021)
Today, commercial banks are becoming the central link in the market system. They account for the bulk of non-cash settlements, they are responsible for the most important settlement and payment function in the payment system of the state. Banks are today the main institution of the financial system for the accumulation of funds and lending to all economic entities. A special place belongs to banks in the rapidly developing sphere of financial services to the population. Thus, none of the segments of the global and national financial markets can do without the participation of commercial banks. When attracting funds, the bank needs to guarantee the return of the attracted resources, assess all risks, make sure of the client's creditworthiness and form a fund for possible loan losses. Credit risk management is one of the main directions in the process of banking. Successful risk management in the implementation of the bank's financial policy is possible only with the use of the best world methods. This system must be flexible in management and comply with all technological trends and threats that arise in such a dynamically changing modern world. In this article, we will analyze the risk management in the activities of the Chinese commercial bank Hua Xia Bank Co., Ltd.
Keywords: Bank; banking; banking services; risk management; banking risks; risk management.